The Peningkatan Kapasitas Usaha Konveksi Melalui Legalisasi Usaha dan Digital Marketing - Kurniawan, Kukuh Dwi; haryanti, agustin dwi; Sheng, Soh Yong (Universitas Muhammadiyah Malang, 2023)
Purpose - MSMEs are business actors who support the economy in Indonesia. Even though they are small, a large number of business actors can produce a tremendous impact on the rotation of the economic wheel. However, it needs to be understood that not all business actors are successful, there are many obstacles that become problems for MSME business actors. For this reason, efforts need to be made to reduce the burden on MSME business actors, without having to wait for government efforts. Design/methodology/approach – The implementation of this service took Dewi Collection partners who are engaged in the convection business located in Jodipan Village, Blimbing District, Malang City. This service consists of two activities carried out, namely, assistance in establishing a business entity in the form of a trading business and assistance in creating social media accounts as a means of digital marketing. Findings - Community service activities increase the capacity of business actors and become influencers for other business actors for the same activities. Originality/value - This treatment generally has positive implications for MSME business actors by increasing the business capacity of business actors. KEYWORDS: Business entity; Convection Business, Digital Marketing; Legalization.